Structure-activity relationship investigation of Phe-Arg mimetic region of human glutaminyl cyclase inhibitors. Issue 12 (23rd July 2018) - Ngo, Van T.H.; Hoang, Van-Hai; Tran, Phuong-Thao; Van Manh, Nguyen; Ann, Jihyae; Kim, Eunhye; Cui, Minghua; Choi, Sun; Lee, Jiyoun; Kim, Hee; Ha, Hee-Jin; Choi, Kwanghyun; et al.
Graphical abstract: Abstract: Glutamyl cyclase (QC) is a promising therapeutic target because of its involvement in the pathogenesis of Alzheimer's disease. In this study, we developed novel QC inhibitors that contain 3-aminoalkyloxy-4-methoxyphenyl and 4-aminoalkyloxyphenyl groups to replace the previously developed pharmacophore. Several potent inhibitors were identified, showing IC50 values in a low nanomolar range, and were further studied for in vitro toxicity and in vivo activity. Among these, inhibitors 51 and 53 displayed the most potent AβN3pE−40 -lowering effects in in vivo acute model with reasonable BBB penetration, without showing cytotoxicity and h ERG inhibition. The molecular modeling analysis of 53 indicated that the salt bridge interaction and the hydrogen bonding in the active site provided a high potency. Given the potent activity and favorable BBB penetration with low cytotoxicity, we believe that compound 53 may serve as a potential candidate for anti-Alzheimer's agents.